Change in goal orientation of Korean high school athletes: A cross-temporal meta-analysis, 1999–2014. (May 2016) - Park, Yoobin; Kim, Taek-Su; Park, Sun W.
Abstract: This study examined changes in ego and task orientation scores on the Task and Ego Orientation in Sport Questionnaire (Duda, 1989, 1992) among Korean high school athletes. Ego-oriented individuals focus on achieving superiority while those who are task-oriented place importance on personal mastery. A cross-temporal meta-analysis of 34 studies (total N  = 6, 503) was conducted, and a significant rise was found in young Koreans' ego orientation between 1999 and 2014. The mean ego orientation scores were significantly correlated with year of data collection when weighted by sample size (β = .49). Since 1999, ego orientation scores have increased by 0.64 standard deviations. Task orientation scores were unrelated to ego orientation scores and showed no apparent pattern of change over time. Highlights: This study examined changes in ego and task orientation among Korean high school athletes. It was found that ego orientation has increased over the past few decades. Task orientation was unrelated to ego orientation and showed no apparent pattern of change. Social, economic, and cultural influences on achievement motivation were discussed.